The Influence of Employee Creativity and Job Involvement on Competitive Advantage Mediated by Strategic Planning at PT Nesinak Industries - Usliani, Usliani; Setyaningrum, Retno Purwani (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2023)
The purpose of this study was to determine the direct and indirect effects between the variables of employee creativity and job involvement variables mediated by strategic planning on competitive advantage. This research was conducted using a quantitative method approach. The sample used in this study was 90. Data collection was used by distributing questionnaires. The research results show that employee creativity (X1) has a positive influence on competitive advantage (Y) with a t-statistic value (5,570 > 1,96), work involvement (X2) has no influence on competitive advantage (Y) with a t-statistic value (1,685 < 1,96), strategic planning (Z) has no influence on competitive advantage (Y) with a t- statistic value (1,258 < 1,96), employee creativity (X1) has a significant influence on strategic planning (Z) with a t-statistic value (2,609 > 1,96), work involvement (X2) has a positive influence on strategic planning (Z) with a t-statistic value (5,934 > 1,96), employee creativity (X1) mediated by planning strategy (Z) has no influence on competitive advantage (Y) with a t-statistic value (0,937 < 1,96), work involvement (X2) mediated by strategic planning (Z) has no influence on competitive advantage (Y) with a t-statistic value (1,298 < 1,96).